Attitude and Perception of Academic and Administrative Staff towards Progression in Higher Institutions of Learning in Ghana - Gladys, Diedong; Adams, Abdulai; Alhassan, Eliasu (Asian Journal of Contemporary Education, 2018)
The continuous development of staffs of higher institutions of learning is crucial in the attainment of institutional and national goals on quality education. This study analysed the attitude and perception of staff of the University for Development Studies (UDS) aimed at uncovering how issues of motivation impact on their performance. Data were collected from 44 lecturers and administrators across the three main faculties of the Wa campus of the institution using a semi-structured questionnaire. A participatory rating method using a 5-point Likert-scale was used. Findings revealed that staff of the institution are well motivated to perform their jobs. The majority of staff are unhappy with the issue of promotions in the system, which many perceived to be unfair, not transparent, and characterised by delays. The results show that increasing access to updated training, improving the physical work environment for staff and strengthening work supervision are areas that need improvement for staff progression. The study recommends that management of the institution as well as policymakers in the educational sector should take a keen interest in staff welfare issues by investing more in capacity building and basic infrastructure.